2023
DOI: 10.3390/ma16114145
|View full text |Cite
|
Sign up to set email alerts
|

Biological Response of Human Gingival Fibroblasts to Zinc-Doped Hydroxyapatite Designed for Dental Applications—An In Vitro Study

Madalina Andreea Badea,
Mihaela Balas,
Marcela Popa
et al.

Abstract: This study aimed to investigate the biological response induced by hydroxyapatite (HAp) and zinc-doped HAp (ZnHAp) in human gingival fibroblasts and to explore their antimicrobial activity. The ZnHAp (with xZn = 0.00 and 0.07) powders, synthesized by the sol-gel method, retained the crystallographic structure of pure HA without any modification. Elemental mapping confirmed the uniform dispersion of zinc ions in the HAp lattice. The size of crystallites was 18.67 ± 2 nm for ZnHAp and 21.54 ± 1 nm for HAp. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
0
0
Order By: Relevance
“…The preliminary findings gathered from the MTT cytotoxic assays were in good agreement with previous studies that reported data on the biological properties of hydroxyapatite and hydroxyapatite-based composites [39,[49][50][51][52]. In their previously reported studies on the "Biological response of human gingival fibroblasts to zinc-doped hydroxyapatite designed for dental applications-an in vitro study", Badea et al [53] highlighted that the decrease observed in cell viability was influenced by the concentration of the nanoparticles. Their findings suggested that the lowest number of cell viability was obtained after the cells were exposed to 500 µg/mL of ZnHAp and 62.5 µg/mL for HAp NPs.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The preliminary findings gathered from the MTT cytotoxic assays were in good agreement with previous studies that reported data on the biological properties of hydroxyapatite and hydroxyapatite-based composites [39,[49][50][51][52]. In their previously reported studies on the "Biological response of human gingival fibroblasts to zinc-doped hydroxyapatite designed for dental applications-an in vitro study", Badea et al [53] highlighted that the decrease observed in cell viability was influenced by the concentration of the nanoparticles. Their findings suggested that the lowest number of cell viability was obtained after the cells were exposed to 500 µg/mL of ZnHAp and 62.5 µg/mL for HAp NPs.…”
Section: Resultssupporting
confidence: 86%
“…Polymers 2023, 15, x FOR PEER REVIEW 14 of 18 designed for dental applications-an in vitro study", Badea et al [53] highlighted that the decrease observed in cell viability was influenced by the concentration of the nanoparticles. Their findings suggested that the lowest number of cell viability was obtained after the cells were exposed to 500 µg/mL of ZnHAp and 62.5 µg/mL for HAp NPs.…”
Section: Resultsmentioning
confidence: 99%
“…occupying lattice sites originally held by Ca 2+ ions, and anionic substitutions, occurring either at hydroxyl (e.g., F − and Cl − ) or phosphate (e.g., AsO 4 3− , SiO 4 4− , and CO 3 2− ) sites or at a combination of both. The presence of these dopants in the structure of nanoHAp results in modifications in the chemical, physical, biological, and mechanical properties [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%